Efektivitas Teknik Self Regulated Learning Dalam Mereduksi Tingkat Kejenuhan Belajar Mahasantri Angkatan 2020 PPA Ibnu Katsir Jember - Latifah Nur; Nasruliyah Hikmatul Maghfiroh; Imaratul Ulwiyah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
The continuous learning process carried out by students is accompanied by pressures, both from within themselves and their environment to achieve maximum learning achievement which can ultimately lead students to learning saturation. In the end, students experience physical and emotional (mental) fatigue, increased depersonalization and decreased academic confidence. This study aims to reduce learning saturation of mahasantri when studying dirosah Islamiyah at PPA Ibnu Katsir Jember. This study uses a quantitative approach with the type of research used true-experiment with pretest-posttest control group design. Sampling in this study using purposive sampling and data analysis method used is Wilcoxon test. The results showed that the mahasantri saturation decreased. That is with an average pretest of 138.28 and an average posttest of 109.57 from this data it can be concluded that there is a decrease from the pretest and posttest results, which means that the treatment provided by researchers in the form of self-regulated learning techniques has succeeded in reducing the level of boredom in learning PPA Ibnu Katsir Jember students. And also supported by the results of the Wilcoxon Test with a value of N = 7a, which means that 7 respondents experienced a decrease in high learning saturation. The mean rank value = 4.00 is the score of the decrease value. While the sum of rank = 28 is the total value. Based on the results of the Wilcoxon test calculation, the value is -2.366, p <.05. So it can be concluded that there is a decrease in learning saturation of PPA Ibnu Katsir Jember mahasantri after counseling services with self-regulated learning techniques